An overview of TCP analysis over routing protocols in wireless mesh network - Mohd Alif Hasmani, Abd Ghani (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org